Peran Lembaga Bantuan Hukum Dalam Memberikan Bantuan Hukum Bagi Masyarakat - Hasan, Zainudin; Renaldy, Daffa (Universitas Batanghari Jambi, 2025)
As a country governed by the rule of law, Indonesia has a complex and complicated legal system, which can make it difficult for people to obtain good legal services. One of the main obstacles to the implementation of law in society is the low level of legal knowledge among the public. Due to their limitations, disadvantaged groups are more vulnerable to prejudice, marginalization, and abuse when fighting for justice. This situation makes it difficult, if not nearly impossible, for them to obtain their rights related to the principles of justice, legal certainty, and balance. This study aims to explore the role of LBH in providing access to justice for the community. Using a descriptive qualitative method, this study found that LBH provides extensive legal assistance, both through litigation and non-litigation. This assistance includes legal assistance, consultation, mediation, and legal education. The results of the study show that LBH plays an important role in empowering disadvantaged communities to understand and fight for their legal rights, thereby increasing access to fair and equal justice.